Study of Final Business Case Sensitivity Analysis in the Government and Business Entity Cooperation (KPBU) Project in the Drinking Water Sector - Jasmin, Feby Wucika; Ophiyandri, Taufika; Hidayat, Benny (Universitas Negeri Padang, 2024)
The purpose of this study is to analize sensitivity of the final business case in public private partnership (PPP) projects. The outcome of this study will provide an overview and limits on changes in the parameters forming the investment. Therefore, a sensitivity analysis was carried out to changes in price, initial cost and interest. The results of the study shows the three changes show that the most sensitive parameter is price changes. Meanwhile, due to the decrease in absorption volume at the offtaker in Jakarta, two efforts were made, namely by increasing the minimum tariff to Rp. 3,846, - or by increasing the concession period to 45 years, this project can be said to be investment worthy.